Formalised definition of communicational spaces. (1st January 2014) - Ahamer, Gilbert
This article deals with the concept of communicational spaces and tries to renew, clarify and formalise it from mathematical, geographical and philosophical standpoints. Starting from the concept that space is constituted by communication, a mathematical formulation of space is sought. In a similar manner to quantum mechanics, the present deliberation attempts to provide more generalised theories of reality than did preceding theories of space. In some approaches, spaces are intrinsically constituted by metrics, mainly by definitions of distance. The triangle inequality seems to be constitutive for space; however, it might no longer be applicable in spaces mediated by internet communication. The recent shift to virtual spaces and recent redefinitions of thirdspaces in human geography lead to a fundamental reconsideration of what space is at all, including drawing on distant philosophies. Concluding, this paper posits not that manifoldness is embedded in space, but conversely, that space is a product of manifoldness.